2021
DOI: 10.1186/s13717-021-00290-9
|View full text |Cite
|
Sign up to set email alerts
|

Split nitrogen fertilizer application improved grain yield in winter wheat (Triticum aestivum L.) via modulating antioxidant capacity and 13C photosynthate mobilization under water-saving irrigation conditions

Abstract: A water-saving cultivation technique of supplementary irrigation based on soil moisture levels has been adopted for winter wheat production in the Huang-Huai-Hai Plain of China, due to the enhanced water-use efficiency. However, appropriate split nitrogen management may further improve crop growth and grain yield. Here, we conducted a 2-year field experiment to determine if split nitrogen management might improve wheat productivity by enhancing 13C photosynthate mobilization and the antioxidant defense system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…The results were accord with Ullah et al 32 those showed that higher nitrogen increased the plant height of wheat crop. Research showed that recommended N (130 kg N ha −1 ) produced a maximum dry biomass assimilation after anthesis stage, these findings are in line with previous research of Zhang et al 27 . The results are also accord with Li et al 33 which showed that optimum N and water improved biomass accumulation after anthesis in wheat crop.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were accord with Ullah et al 32 those showed that higher nitrogen increased the plant height of wheat crop. Research showed that recommended N (130 kg N ha −1 ) produced a maximum dry biomass assimilation after anthesis stage, these findings are in line with previous research of Zhang et al 27 . The results are also accord with Li et al 33 which showed that optimum N and water improved biomass accumulation after anthesis in wheat crop.…”
Section: Discussionsupporting
confidence: 91%
“…The S element is also used as a fungicide and secondary nutrient, and neutralizes the alkalinity due to soil acidic properties 26 . Therefore, the monotypic urea cause more leaching and decrease soil fertility resulting in wheat yield reduction 27 , 28 . Neem-coated urea (NCU) has nitrification inhibition characteristics due to its chemical components like azadirachtin, melicians, de-acetyl, and salanin which showed coating percentage-based fertilizers treatments inhibition effects in soils 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The planting densities associated with P1, P2, and P3 were 5.6 × 10 4 , 6.1 × 10 4 , and 7.3 × 10 4 plants ha −1 , respectively. Each planting pattern had two N applications: 240 kg N ha −1 (N 240 ) and 120 kg N ha −1 (N 120 ) to cover the varying N applications used by the local farmers (Zhang et al, 2021); in each treatment, 50% of N fertilizer was broadcasted with 90 kg ha −1 of P 2 O 5 and 75 kg ha −1 of K 2 O as basal fertilizer over each plot, followed by immediate plowing to avoid nitrogen volatilization; the remaining 50% of N fertilizer was applied as top-dressing at early jointing stage in the middle of July. All plots were irrigated with 60 mm of water on June 18 in 2016 and June 15 in 2017, using sprinkler irrigation to facilitate seed germination and emergence.…”
Section: Experimental Site and Plantingmentioning
confidence: 99%
“…The soluble sugar, soluble protein, and activities of POD and SOD have been shown to be significantly increased with N application up to a certain range [19]. Appropriate N rate and time could increase antioxidant capacity, which mitigates the toxicity of ROS, eventually leading to photosystem vigor and increased yield [20]. Isozymes catalyze the same chemical reaction, but their protein molecular structure and physicochemical properties are obviously different [21].…”
Section: Introductionmentioning
confidence: 99%